Topographic representation of high-level cognition: numerosity or sensory processing? - Gebuis, T; Gevers, W; Cohen Kadosh, R (2014)
A recent study showed that topographic field maps of complex cognitive functions, such as numerosity, exist in the human brain. This is an exciting, novel approach for studying the neural representation of high-level cognition. However, the results can also be explained on the basis of the confounding non-numerical sensory cues of numerosity.